2005
DOI: 10.1590/s0034-70942005000500012
|View full text |Cite
|
Sign up to set email alerts
|

Proteção miocárdica em cirurgia cardíaca

Abstract: The association of adequate anesthetic technique using heart protecting agents to usual myocardial protection modalities performed by the surgeon may contribute to the prevention of cardiac surgery-induced myocardial dysfunction and improve postoperative outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 121 publications
(234 reference statements)
0
2
0
1
Order By: Relevance
“…Os radicais hiperóxidos compreendem o ânion superóxido (O -²), o radical hidroxila (OH) e o peróxido de hidrogênio (H²O²), as quais são removidos das células por sistemas de enzimas com funções antioxidantes, normalmente presentes na fisiologia miocárdica. Esses sistemas de enzimas endógenas com ação antioxidante são responsáveis pela limitação do acúmulo intracelular de O -² e H²O² durante o metabolismo normal, reduzindo o dano oxidativo sobre proteínas e lipídeos [2][3][4] . Para melhorar a proteção miocárdica durante procedimentos que envolvam injúria de reperfusão, recentemente as atenções voltaram-se para a pesquisa de drogas citoprotetoras com ação em segmentos do metabolismo celular, utilizadas isoladamente ou em associação para reduzir ou prevenir o dano sobre a célula cardíaca 5,6 .…”
Section: Introductionunclassified
“…Os radicais hiperóxidos compreendem o ânion superóxido (O -²), o radical hidroxila (OH) e o peróxido de hidrogênio (H²O²), as quais são removidos das células por sistemas de enzimas com funções antioxidantes, normalmente presentes na fisiologia miocárdica. Esses sistemas de enzimas endógenas com ação antioxidante são responsáveis pela limitação do acúmulo intracelular de O -² e H²O² durante o metabolismo normal, reduzindo o dano oxidativo sobre proteínas e lipídeos [2][3][4] . Para melhorar a proteção miocárdica durante procedimentos que envolvam injúria de reperfusão, recentemente as atenções voltaram-se para a pesquisa de drogas citoprotetoras com ação em segmentos do metabolismo celular, utilizadas isoladamente ou em associação para reduzir ou prevenir o dano sobre a célula cardíaca 5,6 .…”
Section: Introductionunclassified
“…In this way, the main determinants of post-ischemia ventricular function recovery are the duration and severity of ischemia, in addition to post-ischemia reperfusion, which may be present or not, leading to ischemic contracture of the left ventricle (stone heart) [28]. Based on this knowledge and on the description by Heyndrickx et al, in 1975, it is observed that the myocardial depression after ischemia/reperfusion is generated by two factors: through oxygen-derived free radicals binding released at the moment of reperfusion and through increased calcium intracellular concentration (calcium overload), which occurs during both ischemia and reperfusion, leading to severe systolic and diastolic dysfunction which can last minutes or days after cardiac surgery, bringing up the need to protect the myocardium during cardioplegia [3].…”
Section: Myocardial Protectionmentioning
confidence: 99%
“…In this way, throughout cardiac surgery history, the increasing need of myocardial protection follows its evolution, imposing challenges to all those who dedicate themselves to the specialty in developing techniques and drugs that increase the myocardium tolerance to ischemic periods, including pharmacologists, physiologists, pathologists, perfusionists, anesthesiologists, and surgeons [2], thus contributing to better preserve myocardial function [3], i.e., to allow interrupting its electromechanical activity without producing either structural or functional injury aiming at to facilitate the repair of existing cardiac lesions.…”
Section: Introductionmentioning
confidence: 99%